Open Access Publishing as a Para-Academic Proposition: OA as Labour Relation - Paul F Boshears (tripleC: Communication, Capitalism & Critique)
In this commentary, I ask what is meant by the phrase Open Access (OA)? If OA publishing has emancipatory potential for the publics that are thought to benefit from the practice, why is there so much business as usual? Para-academic practices are about affirming scholarship as a symptom and creating a common good, creating a public knowledge that is a knowledgable public. It is because OA shares this concern for publics that para-academic practices include OA publishing. By debating the merits of, experimenting with, and invigorating our understanding of OA I believe para-academic practices become more apparently necessary because ultimately OA, like Academia, is haunted by the figure of the public as an already-formed thing.